Looking at Britain - Gadsby, Jean & David; Nang Chan Yeema (London, England A & C Black Publishers Ltd., 1981)
This book explains how the people if Britain earn their living, in industry, farming, fishing, transport and communications.
Keywords: Adult Nonfiction